Integrin factor (FAM27E3), as a metastatic marker of papillary thyroid carcinoma, through the p53 signaling pathway promoting lymph node metastasis - Zhang, Dong; Xiang, Kai-Fang; Hong, Chen-Chen; Bao, Xiao-Ping; Wu, Yan; Wu, Rui (Frontiers in Genetics, 2025)
BackgroundPapillary thyroid carcinoma (PTC) has a lymph node metastasis rate of 20%–90%. This study aims to explore the role and regulatory mechanism of the FAM27E3 in PTC lymph node metastasis.MethodThe seven thyroid cancer (THCA) datasets from the Gene Expression Omnibus (GEO) were combined as the training group, while the PTC dataset served as the testing group. Venn analysis identified overlapping genes through consistent cluster analysis and weighted gene co-expression network analysis (WGCNA). We used the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases to perform gene set enrichment analysis (GSEA) to explore the enriched terms. Least absolute shrinkage and selection operator (LASSO) analysis was applied to the overlapping genes to identify key influence factors. Finally, FAM27E3 was used for score analysis (epithelial–mesenchymal transition (EMT), angiogenesis, and mRNAsi scores). Immune cell infiltration was assessed using the CIBERSORT algorithm. CCK8, colony formation, Transwell assays, Western blotting, and RT-PCR were employed to evaluate cell viability, invasion, migration, and gene/protein expression.ResultsThe clustering method distinguished the samples into two subtypes. We obtained the mRNA expression levels of 128 overlapping genes from the tumor and C1 modules of the GSE60542 dataset. FAM27E3 was identified as a hub gene associated with PTC lymph node metastasis and had a significantly positive correlation with EMT_score. The MRNAsi_score was increased in the FAM27E3 high-expression group. A high expression of FAM27E3 indicated a reduction in the overall macrophage levels. FAM27E3 exhibited high expression in PTC cell lines, and its downregulation suppressed cell proliferation, migration, and invasion. FAM27E3 promoted the lymph node metastasis of PTC, which was associated with the p53 signaling pathway.ConclusionFAM27E3, as a marker for PTC lymph node metastasis, promotes PTC lymph node metastasis related to the p53 signaling pathway.